Bacterial Diversity Associated with Terrestrial and Aquatic Snails - Konstantinos Apostolou; Canella Radea; Alexandra Meziti; Konstantinos Ar. Kormas (Microorganisms)
The introduction of the holobiont concept has triggered scientific interest in depicting the structural and functional diversity of animal microbial symbionts, which has resulted in an unprecedented wealth of such cross-domain biological associations. The steadfast technological progress in nucleic acid-based approaches would cause one to expect that scientific works on the microbial symbionts of animals would be balanced at least for the farmed animals of human interest. For some animals, such as ruminants and a few farmed fish species of financial significance, the scientific wealth of the microbial worlds they host is immense and ever growing. The opposite happens for other animals, such as snails, in both the wild and farmed species. Snails are evolutionary old animals, with complex ecophysiological roles, living in rich microbial habitats such as soil and sediments or water. In order to create a stepping stone for future snail microbiome studies, in this literature review, we combined all the available knowledge to date, as documented in scientific papers, on any microbes associated with healthy and diseased terrestrial and aquatic snail species from natural and farmed populations. We conducted a Boolean search in Scopus, Web of Science, and ScienceDirect until June 2024, identifying 137 papers, of which 60 were used for original data on snail bacterial communities in the gastrointestinal tract, hepatopancreas, and feces. We provide a synthesis on how representative this knowledge is towards depicting the possible snail core microbiota, as well as the steps that need to be taken in the immediate future to increase the in-depth and targeted knowledge of the bacterial component in snail holobionts.